Caribbean Report 10-01-1995 - Ransome, Debbie (anchor); Yearwood, Robin (interviewee); Mardon, Clive (correspondent); Guilford, Peter (interviewee); Rohee, Clement (interviewee); Rush, George (correspondent); Cole, Andy (interviewee); Ferguson, Alex (interviewee) (The British Broadcasting Corporation, 1995)
This report examines the draft proposal put forward by the Acker/Loeb Group on the privatization of LIAT. The governments of Trinidad and Tobago and Antigua/Barbuda were given the mandate to upgrade the airline. The Antigua/Barbuda Aviation Minister Robin Yearwood was interviewed on the pending divestment. Clive Marden reports on Europe's response to US concerns about the banana regime. The US claims that Europe is discriminating against American banana companies by restricting imports which cost them millions of dollars. Peter Guilford, EU spokesman, indicated that any unilateral action on the part of the US would be viewed very seriously. Guyana's Foreign Minister Clement Rohee has revived interest in the Manning Initiative, inviting his counterparts from Barbados and Trinidad and Tobago to renew talks on this three way confederation. The Manning Initiative was put forward as a step towards economic as well as political union among the three CARICOM states, Barbados, Guyana and Trinidad and Tobago. Debbie Ransome interviews Mr. Rohee on Guyana's sudden enthusiasm on this idea and what this means for CARICOM relations. In Bermuda, the planned appointment of a new British Commissioner of Police and Deputy Commissioner has provoked debate within the society. George Rush reports on the situation as a petition has been started to appoint a local candidate to the post. The Senate of Puerto Rico has joined with Caribbean states objecting to the transportation of nuclear wastes through the Caribbean Sea by a Japanese ship. They have called upon the United Nations to investigate the issue of global traffic in plutonium and other dangerous materials. Andy Cole became the most expensive player in the history of British football when he moved from New Castle to Manchester United. Both Andy Cole and Alex Ferguson, Manager of Manchester United were questioned on this move. The report ends with the announcement of the death of the former Principal of St. Augustine Campus, Professor Lloyd Brathwaite, in Trinidad.
1. Headlines with Debbie Ransome, anchor (00:00-00:25)
2. Report on the draft proposal for the privatization of LIAT (00:26-00:58)
3. Interview with Robin Yearwood on the privatization of LIAT (00:59-04:22)
4. Report on the US concerns on Europe's banana regime (04:23-04:47)
Keywords: Airlines -- Privatization; Airlines -- Management; Airlines -- Caribbean, English-speaking; Banana trade -- Latin America; Bananas -- Economic aspects; European Union countries -- Economic policy; Import quotas -- European Union countries; United States -- Commerce -- European Union countries; Regionalism -- Caribbean Area; Caribbean Area -- Politics and government; Caribbean Area -- Economic integration; Caribbean Area -- Political aspects; Police -- Bermuda Islands; Bermuda Islands -- Foreign relations -- Great Britain; Hazardous wastes -- Caribbean Area; Radioactive waste disposal -- Caribbean Area; Hazardous wastes -- Transportation -- Caribbean Area; Soccer -- Management; Soccer players -- Great Britain; Soccer teams -- England -- Manchester; Death; College administrators -- Trinidad and Tobago; Universities and colleges -- Faculty